Enhanced performance of InAs-based interband cascade lasers emitting between 10–13 µm. (1st February 2023) - Massengale, Jeremy A; Shen, Yixuan; Yang, Rui Q; Hawkins, Samuel D; Klem, John F
Abstract: Interband cascade lasers (ICLs) based on the type-II quantum well (QW) active region have attracted much attention for a range of practical applications in the mid-infrared due, in part, to their low power consumption. However, extending the operating wavelength of these ICLs into the long-wave infrared region presents several challenges including the reduced thermal conductivity of the optical cladding layers and the diminished wavefunction overlap in the type-II QW. One solution to alleviate the former concern is to use InAs-based ICLs. To solve the latter problem, InAs0.5 P0.5 barriers are introduced in the active region, which lowers the electronic energy level and allows for the InAs well width to be reduced at longer emission wavelengths. Here the advancement of long wavelength ICLs, made from four new InAs-based ICL wafers grown by molecular beam epitaxy, is reported. These ICLs lased in the wavelength range from 10 to 13 µ m and showed significantly improved performance compared with previous ICLs, including the first demonstration of broad-area devices operating in continuous wave mode beyond 12 µ m. These ICLs exhibited substantially increased output powers with reduced threshold voltages ( V th ) and current densities ( J th ). They operated at temperatures up to 40 K higher than previous ICLs at similar wavelengths.